History and Development of Water Treatment for Human Consumption - Philippe Hartemann; Antoine Montiel (Hygiene)
Throughout history, humans have sought to drink water that is good for their health, according to the knowledge of the time. Hippocrates’ definition of water quality, “good water should be clear, light, aerated, without any perceptible odor or taste, warm in winter and cold in summer”, remained virtually unchanged until 1887, when it was added that water should dissolve soap and foam well, be clear and colorless, have a pleasant taste, leave no large deposits after boiling, and cook vegetables and wash clothes well. This definition guided all treatments to remove the substances responsible for cloudiness, odor and discoloration, as well as the choice of resources: clear water and water with low mineral content. The discoveries by Pasteur and Koch led to the addition of microbiological criteria, like the absence of pathogens, and the definition of microbiological indicators. Throughout the 20th century, advances in scientific knowledge in microbiology, chemistry and toxicology led to major progress in treatment methods. These filtration and disinfection treatments are described here according to their historical implementation. Due to progress in numerous areas, e.g., both chemical and microbiological analytical detection limits, speed of information flow and origins of certain diseases that are discovered to be waterborne, the consumer is now exposed to anxiety-provoking news (microplastics, eternal pollutants (cf. per- and polyfluoroalkyl substances (PFASs)), drugs, pesticides residues, etc.). Thus, the consumer tends to lose confidence in tap or bottled water and turn to buying home purifiers. Drinking water treatment will continue to evolve with more sophisticated processes, as analytical progress enables us to expect further developments.